Exposure Pathways to Antimicrobial Resistance at the Human-Animal Interface—A Qualitative Comparison of Swiss Expert and Consumer Opinions - Lechner, Isabel; Freivogel, Claudia; Stärk, Katharina D. C.; Visschers, Vivianne H. M. (Frontiers in Public Health, 2020)
Antimicrobial resistance (AMR) is an emerging global health concern, affecting both the animal and the human population. Transmission pathways of AMR are therefore abundant and complex, and ways to prevent or reduce transmission to consumers must be identified. The overall goal of this study was to define the content of an intervention study aimed at reducing the transmission of AMR from animal sources to humans. To identify the most relevant pathways, Swiss experts and consumers were interviewed about their opinions on the risks of transmission of AMR. Opinions of experts and consumers were then qualitatively compared and the main gaps identified. The results revealed that Swiss consumers had several misconceptions regarding the sources and transmission of AMR, and that they in particular underestimated the importance of poultry meat and pets as a potential source of AMR. Furthermore, high uncertainty was noted in experts regarding the prevalence of AMR in pets and the potential of transmission to their owners. Consequently, awareness of AMR transmission pathways should be increased among consumers to overcome common misconceptions, which will help reduce the risk of transmission. Further research is needed to better understand the pets' potential to harbor and transmit AMR to their owners, and to identify most effective methods to increase risk awareness in consumers as well as intervention strategies promoting consumer behaviors to mitigate AMR transmissions at the human-animal interface.